Low doses of radiation: epidemiological investigations - Dikiy, N.P.; Dovbnya, A.N.; Medvedeva, E.P. (Вопросы атомной науки и техники, 2013)
Influence of small dozes of radiation was investigated with the help epidemiologic evidence. Correlation analysis, regression analysis and frequency analysis were used for investigating morbidity of various cancer illnesses. The pollution of the environment and the fallout of radionuclides in 1962 and 1986 years have an influence upon morbidity of cancer. Influence of small dozes of radiation on health of the population is multifactorial. Therefore depending on other adverse external conditions the influence of radiation in small dozes can be increased or is weakened. Such character of influence of radiation in small dozes proposes the differentiated approach at realization of preventive measures. Especially it concerns regions with favorable ecological conditions.